Peningkatan Pengetahuan dan Keterampilan Perawatan serta Perbaikan Mesin Klotok Bagi Masyarakat Nelayan - Sukardi Sukardi; Muhammad Hudan Rahmat; Sri Murwantini; I Made Supatra; Ahmad Eko Suryanto; Steven Yolando; Wiyogo Wiyogo; Agung Samudra; Supriyadi Supriyadi; Galfri Siswandi; Debora Debora; Harie Satiyadi Jaya; Vontas Alfeny Nahan; Diki Cahyoko; Gabriel Alfrans Valentino Juli (Fakultas Teknik Universitas Palangka Raya, 2026)
The lack of technical knowledge regarding klotok engine maintenance among fishermen in the Kahayan River Basin results in a high risk of operational damage. This Community Service Program aims to improve fishermen's skills through theoretical and practical training in klotok engine repair. The program's main advantage lies in its sociocultural approach to correcting technical misconceptions, namely by aligning academic terms with local terminology that is easily understood by the local community. The results of an evaluation of 11 participants showed that this approach effectively increased participant knowledge with an N-Gain of 0.405 and achieved a satisfaction level of 87.27%. The practical implication of this finding is the recommendation to develop a machine maintenance guide module that adopts local language and terms as a self-learning reference for fishermen.